C. Silva-Corvalán y A. Enrique-Arias, Sociolingüística y pragmática del español. Segunda edición. Washington DC, Georgetown University Press, 2017, 410 pp. - Albitre Lamata, Paula (Estudios Humanísticos. Filología, 2020)
Resumen/abstract